The culture of entertainment and the Spanish novel of the 21st century (XXI Century. Spanish Literature and Culture, 2004)
This work reviews the most noteworthy Spanish novels of 2003. The article offers up a review of each novel, taking into account different thematic and formal aspects. Along with authors of large literary trajectories, readers will discover other who, through the sheer quality work alone, will delight them.
Keywords: novel; narrative; fiction; reality; recent history